Buffy the vampire slayer: what being Jewish has to do with it - Stratton, Jon (Sage Publications, 2005)
This article examines the whiteness in the television series Buffy the Vampire Slayer. The author argues that the show’s overwhelming whiteness is a product of a generalized white anxiety about the numerical loss of white dominance across the United States and, in particular, in California. The article goes on to think through the role that Jewishness plays in the program, discussing the relationship between the apparently Anglo-American Buffy, played by a Jewish actor, and her sidekick, Willow, who is characterized as Jewish but is played by a non-Jewish actor. The evil master in the first series is given Nazi characteristics and the destruction that he wants to inflict carries connotations of the Holocaust. Structurally, Buffy is produced as the Jew who saves the United States from this demonic destruction. In this traumatic renarrativising, the Holocaust comes to stand for the white-experienced crisis of the loss of white supremacy in the United States. With this reading we can begin to understand the show’s popularity among early adult, predominantly white Americans.